2002
DOI: 10.1074/jbc.m110627200
|View full text |Cite
|
Sign up to set email alerts
|

Guanylin, Uroguanylin, and Heat-stable Euterotoxin Activate Guanylate Cyclase C and/or a Pertussis Toxin-sensitive G Protein in Human Proximal Tubule Cells

Abstract: Membrane guanylate cyclase C (GC-C) is the receptor for guanylin, uroguanylin, and heat-stable enterotoxin (STa) in the intestine. GC-C-deficient mice show resistance to STa in intestine but saluretic and diuretic effects of uroguanylin and STa are not disturbed. Here we describe the cellular effects of these peptides using immortalized human kidney epithelial (IHKE-1) cells with properties of the proximal tubule, analyzed with the slow-whole-cell patch clamp technique. Uroguanylin (10 or 100 nM) either hyperp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
56
0
3

Year Published

2003
2003
2009
2009

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(69 citation statements)
references
References 41 publications
(36 reference statements)
10
56
0
3
Order By: Relevance
“…Potthast et al (54) localized GC-C in the mouse kidney only in glomeruli and proximal tubules. In the human kidney, we detected GC-C again only in the kidney cortex and specifically in proximal tubules ( Figure 6) (60,61). In contrary to these findings in mouse and human, in rat kidney, Carrithers et al (58) found mRNA for GC-C in all nephron segments, suggesting differences in tissue distribution of GC-C in different species.…”
Section: Signaling Mechanisms Of Guanylin Peptides In the Kidneymentioning
confidence: 45%
See 3 more Smart Citations
“…Potthast et al (54) localized GC-C in the mouse kidney only in glomeruli and proximal tubules. In the human kidney, we detected GC-C again only in the kidney cortex and specifically in proximal tubules ( Figure 6) (60,61). In contrary to these findings in mouse and human, in rat kidney, Carrithers et al (58) found mRNA for GC-C in all nephron segments, suggesting differences in tissue distribution of GC-C in different species.…”
Section: Signaling Mechanisms Of Guanylin Peptides In the Kidneymentioning
confidence: 45%
“…Guanylin peptides increase the intracellular cGMP concentration in a proximal tubule cell line of opossum kidney (OK cells) via the opossum kidney GC-C (OK-GC), which is the analog to the human GC-C (62). Recently, we demonstrated an increase in the cellular cGMP concentration induced by guanylin peptides also in a human proximal tubule cell line (IHKE1) (61). In this cell line, GN and UGN also activated GC-C.…”
Section: Signaling Mechanisms Of Guanylin Peptides In the Kidneymentioning
confidence: 96%
See 2 more Smart Citations
“…However, the former was more detected and the total amount of uroguanylin bioactivity was increased as shown in Figure 2. Because uroguanylin has another cGMP-independent pathway unlike ANP (22) and downregulates the message for the Na ϩ /K ϩ ATPase ␥-subunit in mice (23), uroguanylin may be a candidate of natriuretic factor for nephrotic animals. However, ANP was previously suspected to be a causative factor for sodium retention in nephrotic syndrome.…”
Section: Discussionmentioning
confidence: 99%